Institutional reform in Myanmar: preventing corporate land rights abuses - Aguirre, Daniel (International journal of transitional justice, 2021)
In 2011, after five decades of authoritarian rule, Myanmar accelerated its military-guided transition, culminating in partially democratic elections in 2015. While land reform was a central part of protest that led to governmental changes, unlawful land confiscation and forced evictions remain central obstacles to transition in Myanmar. The current government has failed to reform the legal framework, institutions, policy and practice violating Housing, Land and Property (HLP) rights. While civil society has called for participatory and accountable institutions, a perceived need to appease the military, to harness the economic power of ‘crony’ businesspeople and to attract foreign investment has left violations of HLP rights inadequately addressed. This article argues that transitional justice’s guarantees of non-reoccurrence are essential to the protection of HLP rights in Myanmar, and that the best method of preventing reoccurrence is through upholding the state duty to protect human rights by reforming laws and institutions.